Meningkatkan Kemampuan Motorik Kasar Melalui Permainan Galasin di Taman Kanak-Kanak Negeri Pembina Santur Kota Sawahlunto - Afriani, Depta; Marlina, Serli (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This research aims to improve children's gross motor skills through galasin games at the Pembina Santur State Kindergarten, Sawahlunto City. This research uses the Classroom Action Research (PTK) method which is carried out in two cycles, each consisting of three meetings. The research subjects were 10 children aged 4-5 years. Data was collected through observation and documentation, then analyzed using percentage techniques. The results of the study showed an increase in children's gross motor skills, especially in indicators of strength, balance, agility and coordination, with an average success percentage reaching more than 75% at the end of the second cycle. Thus, the galasin game is effective in improving children's gross motor skills.